Viet Nam Alive & Thrive Baseline Survey 2010: Facility Assessment - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the facility assessment survey that was conducted to gather data at baseline within the context of an overall evaluation of the franchise model for Alive & Thrive (A&T) in Viet Nam. The overall aims of the evaluation were to assess the impact of the franchise model on (1) age-appropriate IYCF practices among children <2 years of age and (2) stunting among children 2-5 years of age. A&T is an initiative funded by the Bill & Melinda Gates Foundation to reduce undernutrition and death caused by suboptimal IYCF practices in three countries (Viet Nam, Bangladesh, and Ethiopia) over a period of six years (2009-2014). The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing the stunting of children under two years of age. A&T applied principles of social franchising within the government health system to deliver the interventions. A&T’s Viet Nam strategy is designed to support improvements in infant and young child feeding (IYCF) in three key ways: (1) improving policy and regulatory environments; (2) shaping IYCF demand and practice; and (3) increasing supply, demand, and use of fortified complementary foods. In order to achieve this, the A&T Viet Nam program has been divided into three main focus areas namely advocacy, community, and the private sector. In addition, a communications component is integrated into each of these focus areas to support their activities. Among several activities, the franchise model is a core initiative of the community model to provide quality nutrition counseling to women and families at health facilities at all levels. Implemented in cooperation with the Vietnamese government and select private clinics, franchises will deliver a package of focused IYCF counseling services to pregnant women, lactating mothers, and their families, based on a franchise service package. Focused training and capacity building for healthcare workers will be undertaken to enable the health system to provide franchise services. Individualized services will be supported through mass media campaigns aimed at generating demand for franchise services and promoting optimal IYCF practices. The baseline survey was conducted in 40 communes across four provinces, Thai Nguyen, Thanh Hoa, Quang Ngai, and Vinh Long, between June and August 2010 by the IFPRI team in collaboration with the Institute of Social and Medicine Studies (ISMS). The survey included four components—(i) household survey, (ii) community survey, (iii) frontline health workers survey, and (iv) health facility assessments survey. The facility assessment data provide information on existing health facilities such as the number of personnel, services offered and different kind of spaces available at the facility.